Rufomycin Exhibits Dual Effects Against Mycobacterium abscessus Infection by Inducing Host Defense and Antimicrobial Activities - Cho Rong Park; Cho Rong Park; Cho Rong Park; Seungwha Paik; Young Jae Kim; Young Jae Kim; Young Jae Kim; Jin Kyung Kim; Jin Kyung Kim; Sang Min Jeon; Sang Min Jeon; Sang Min Jeon; et al. (Frontiers in Microbiology, 2021)
Nontuberculous mycobacterial pulmonary infection is often aggravated due to antibiotic resistance issues. There is a need for development of new drugs inducing both host immune responses and antimicrobial activities. This study shows that the rufomycins 4/5/6/7 (Rufomycin 4–7), which targets ClpC1 as a subunit of caseinolytic protein complex ClpC1/ClpP1/ClpP2 of mycobacteria, exhibits a dual effect in host innate defense and in vivo antimicrobial activities against a rough morphotype of Mycobacterium abscessus (Mabs-R), a clinically severe morphotype that causes hyperinflammation. Rufomycin 4–7 treatment showed antimicrobial effects against Mabs pulmonary infection in vivo and in macrophages. In addition, Rufomycin 4–7 significantly decreased inflammation, but enhanced the autophagy/lysosomal genes through upregulation of the nuclear translocation of transcription factor EB (TFEB). Furthermore, Rufomycin 4–7 treatment effectively inhibited mitochondrial damage and oxidative stresses in macrophages during Mabs-R infection. Collectively, Rufomycin 4–7-mediated dual effects inducing both antimicrobial activities and host immune defense might confer an advantage to treatment against Mabs-R infection.